Assessment and Mapping of Salt- Affected Soils Using Biophysical Soil Indicators, Rremote Sensing and GIS Analysis in Wadi Elgaab Area Northern State, Sudan - Mohamed , Abass; Abdelwahab, Motasim Hyder; Osman, El Mamoun Haroun; Mohammed, Wael Awad Marajan (European Journal of Applied Sciences, 2023)
Salt-affected soils is a prime indicator of land degradation (LD). Thus, this study was conducted to assess, and mapping of salt-affected soils, evaluating the land suitability for irrigated agriculture and updating information through soil, remote sensing and geographical information system analysis techniques in the study area. By estimating and monitoring some soil properties namely, soil salinity, sodicity and alkalinity, due to drought and LD process. The soil survey was carried for the project area (31105 feddans). This study depends on extracted data and information from soil survey, soil analysis (SA), and remote sensed (RS), in addition to fieldwork (observation points) in the study area. SA and RS data indicated that LD was taken place in the study area particularly in the western, south western and north western parts of the area which were affected by salinity, sodicity and alkalinity. The study showed the study area was highly eroded by wind. According to the framework of the land suitability (FAO, 1990 and 2006), soil properties and degradation hazard, were estimated. The results showed that the soil of the study area is moderately suitable (S2), marginally suitable lands (S3), currently unsuitable land (N1) and unsuitable land for irrigated agriculture (N2), for 15200 feddans, 2580 feddans, 11035 feddans and 2436 feddans respectively.